Kebutuhan Heliport Dalam Operasional Helikopter di Bandara Internasional Sam Ratulangi Manado - Rusman (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2018)
Manado's Sam Ratulangi International Airport serves 70-80 aircraft movements per day, for scheduled and unscheduled fixed wing and rotary wing. In-flight services, there are 2 providers, namely PT Angkasa Pura I as a provider of air side facilities and Perum LPPNPI as an air navigation service provider. The research method was descriptive analysis method, by testing the theory and facts at Sam Ratulangi International Airport in Manado on standard procedures and provisions in the world of aviation. The objective of this research was to examine the surface of the heliport to take safety, efficiency, and safety at Sam Ratulangi International Airport in Manado. The result of this study was the heliport requirements for helicopter operations at Manado's Sam Ratulangi International Airport. Where the heliport was at ground level and equipped with markers and other supporting facilities based on Appendix 14 Volume 2 Aerodrome Heliport and Director General of Civil Aviation Regulation Number: KP 40 in 2015 concerning Technical and Operational Standards Civil Aviation Safety Regulations Part 139 Standard CASR 139).